2016
DOI: 10.12659/ajcr.900829
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Squamous Cell Carcinoma of the Pleura: A Rare Complication of Hidradenitis Suppurativa

Abstract: Patient: Male, 46Final Diagnosis: Metastatic squamous cell carcinomaSymptoms: Short of breathMedication: —Clinical Procedure: Pleural biopsySpecialty: OncologyObjective:Rare diseaseBackground:Squamous cell carcinoma (SCC), also known as Marjolin ulcer, is a rare complication of hidradenitis suppurativa (HS). Metastatic SCC from HS typically involves the axial skeleton or abdominopelvic viscera. Metastatic disease to the lungs is a rare phenomenon with only three reported cases of lung parenchyma. We present a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Many authors describe fatal cases of SCC arising in severe long-standing HS of the perineal and perianal sites or of the buttocks, often complicated by inguinal lymph node metastases [ 35 ]. Joglekar et al reported a case of a 46-year-old male with a history of MU secondary to gluteal HS who developed bilateral pleural effusions, pleural thickening and scattered nodular densities within both lungs concerning for metastatic disease; the wide local excision of sacro-gluteal SCC occurred too late in this case, as the patient already had metastatic disease to inguinal lymph nodes before surgery [ 50 ]. SCC of the perineal area metastatising to the inguinal lymph nodes and to the liver metastases was also reported [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many authors describe fatal cases of SCC arising in severe long-standing HS of the perineal and perianal sites or of the buttocks, often complicated by inguinal lymph node metastases [ 35 ]. Joglekar et al reported a case of a 46-year-old male with a history of MU secondary to gluteal HS who developed bilateral pleural effusions, pleural thickening and scattered nodular densities within both lungs concerning for metastatic disease; the wide local excision of sacro-gluteal SCC occurred too late in this case, as the patient already had metastatic disease to inguinal lymph nodes before surgery [ 50 ]. SCC of the perineal area metastatising to the inguinal lymph nodes and to the liver metastases was also reported [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…2,3 It develops three times more often in males, probably due to the more frequent gluteal and perineal localization in males and is highly associated with smoking. [1][2][3][4] The average period between HS onset and SCC developing is estimated of 27 ± 9.9 years, 1,4 significantly longer than in the presented case (~2.5 years). In addition, cases in medical literature report SCC developing in advanced HS, whereas in the presented case the condition is assessed as hurley I-II.…”
mentioning
confidence: 99%
“…2 On the other hand, the highly malignant nature of this carcinoma determines its poor prognosis. 1,3 The wide surgical excision has an excellent therapeutic result, showing a recurrence rate of only 2.5%, mainly in advanced forms. 5 Complications are relatively mild such as bleeding and forming of hematoma.…”
mentioning
confidence: 99%